(untitled) (Faculty of Education Scientific Journal, 2025)
The study aims to identify the role of the social worker in developing citizenship values ​​and basic skills among students in basic education, The two researchers used the descriptive approach in the style of a social sample survey, and a questionnaire form and a participatory observation tool were used to collect information. The sample size reached (158) individuals, It was drawn by proportional stratified random sampling, and the study reached the most important results, including: The role of the specialist in developing citizenship values ​​is for students to rely on themselves, help them, follow up on the students’ academic level, and cultivate the belief of humanity and equality among students, Among the basic skills that the specialist is keen on is respect for the elderly and compassion for the young. Guiding and advising students, the importance of loyalty and belonging to the homeland, and the skill of creativity and innovation for students.